AB0504 Salivary Interleukin 6 in Primary Sjoegren's Syndrome Mo. (10th June 2014) - Knopf, A.; Drecoll, E.; Becker, K.; Bas, M.; Mansour, N.; Hofauer, B.
Abstract : Background: Primary Sjoegren's syndrome (pSS) represents the most important rheumatic disease affecting the head and neck. Therapeutic regimes usually focus on a supportive therapy using saliva analogues. The progressive clinical course resulting in local complications as bacterial sialadenitis/abscesses, caries, parodontosis or severe dysphagia requires phase dependent therapeutic approaches. Literature lacks detailed assessment of potential biological markers that are able to monitor and modulate disease activity in pSS. Objectives: To assess interleukin 6 (IL-6) as molecular marker to monitor disease activity and to analyze its molecular capacity in disease progression. Methods: 70 patients were diagnosed with pSS according to the AECG criteria. All patients underwent major or minor salivary gland biopsy. IL-6 and related molecules were analyzed using ELISA and Luminex® magnetic bead technology for unstimulated saliva and by immunohistology for formalin fixes samples. Experimental data was related to subjective symptom score and objective clinical parameters that were obtained from all patients. Results: Elevated IL-6 levels were diagnosed in pSS patients while serum IL-6 was regular. Analysis of subjective symptoms revealed a correlation among salivary IL-6 levels and xerostomia (p<0.001) and dysphagia (p=0.038). Objective parameters as gustation test (p=0.001), Schirmer test (p=0.002), unstimulated whole saliva (p<0.039) and lymphatic tissue infiltration (p=0.033) correlated with salivary IL-6 levels. Histological samples identified elevated IL-6 tissue infiltration for serous glandular parenchyma when compared with mixed glandular parenchyma. Patients with clinical disease progression showed rising salivary IL-6 levels and IL-6 levels levelled off during therapy. Conclusions: IL-6 represents an unspecific but sensitive marker of glandular involvement in pSS that reliably monitors subjective and objective disease activity. Our data suggest IL-6 being a key molecule in molecular disease progression. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5877